2015
DOI: 10.1103/physrevlett.115.076402
|View full text |Cite
|
Sign up to set email alerts
|

Collective Modes and Structural Modulation in Ni-Mn-Ga(Co) Martensite Thin Films Probed by Femtosecond Spectroscopy and Scanning Tunneling Microscopy

Abstract: The origin of the martensitic transition in the magnetic shape memory alloy Ni-Mn-Ga has been widely discussed. While several studies suggest it is electronically driven, the adaptive martensite model reproduced the peculiar nonharmonic lattice modulation. We used femtosecond spectroscopy to probe the temperature and doping dependence of collective modes, and scanning tunneling microscopy revealed the corresponding static modulations. We show that the martensitic phase can be described by a complex charge-dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
3
9
0
1
Order By: Relevance
“…This misfit can be closed by stacking faults 12 that are inserted with a substantially larger period than the modulation period. As this stacking fault period is not solely defined by the lattice constants of martensite but also depends on the austenite, the arrangement is incommensurate when measuring a completely martensitic sample, which is in agreement with several diffraction experiments 5 , 22 , 62 . Compared to a periodic stacking sequence, the presence of stacking faults increases the energy of an incommensurate nanotwin arrangement.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This misfit can be closed by stacking faults 12 that are inserted with a substantially larger period than the modulation period. As this stacking fault period is not solely defined by the lattice constants of martensite but also depends on the austenite, the arrangement is incommensurate when measuring a completely martensitic sample, which is in agreement with several diffraction experiments 5 , 22 , 62 . Compared to a periodic stacking sequence, the presence of stacking faults increases the energy of an incommensurate nanotwin arrangement.…”
Section: Resultssupporting
confidence: 87%
“…In modulated structures the atomic positions deviate in a quite periodic way from a simple tetragonal structure. The origin of the modulation is not well-understood, with two competing explanations put forward, so far 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…7. 118 Note that recently the origin of the martensitic transition in the MSMA Ni-Mn-Ga was described by Schubert et al, 128 like a complex charge-density wave tuned by magnetic ordering and strong electron-lattice coupling. Moreover Zhang et al 129 showed the advantage of tailoring the thin film composition so that the magnetostructural martensitic transformation and the FM ordering of the austenitic phase occurred simultaneously.…”
Section: G Fm Shape Memory Alloysmentioning
confidence: 97%
“…In this concept, the modulated structures are described as nanotwinned microstructures of the tetragonal non-modulated (NM) phase that form to minimize the elastic energy at the phase boundary. Alternative models base on Fermi surface nesting [16,17] and phonon softening [18] as driving mechanism. A unified description of both concepts, which is based on the ordering of nanotwin boundaries, was proposed recently [19].…”
Section: Introductionmentioning
confidence: 99%